An Investigation into the Linguistics Representations of the Theme War in Ernest Hemingway's 'For Whom the Bell Tolls" and Bao Ninh's " Nối buồn chiến tranh" ("The Sorrow of War") - Ngô Thị Kim Thoa (2012)
This thesis is an investigation into the theme War’s expressions in Hemingway’s “For Whom the Bell Tolls” and Bao Ninh’s “Nỗi Buồn Chiến Tranh” with the objective of presenting, describing and analyzing the theme War’s ….